Integration of Social Media into Daily Activity of Adolescents and Self-Regulation Characteristics - Dmitry S. Kornienko; Anna Ya. Fominykh; Alexander N. Veraksa; Aidar M. Kalimullin; Yuryi I. Semenov (National Research Mordova State University, 2022)
Introduction. Diverse domains of life become more digitalized, social media (social networks, blogs, and information sharing services) have become an intrinsic element of daily life and activities such as education. Positive and negative consequences of social media use were discovered, which increased the awareness of their involvement in adolescents' and young people's psychological well-being and socializing. However, the characteristics of self-regulation in the context of increased social media usage remain unexplored. The study examined the association between self-regulation characteristics and the degree to which social media is integrated into adolescents' everyday activities. Materials and Methods. The study included 336 teenagers (12-17 years old). Self-regulation features (the SSPM-2020 V.I. Morosanova questionnaire) and social network activity (The scale of integration of social media into daily activity, time spent on it, the numbers of social networks) were assessed. Correlation, comparative, and cluster analyses were used to process the data. Results. The integration of social media into an adolescent's everyday activities varies according to their level of self-regulation. However, formal factors (time and quantity of social networks) do not change between self-regulation levels. Throughout adolescence, social media use is relatively consistent. Girls showed a stronger behavioral and emotional attachment to social media and deeper integration into daily routines. Discussion and Conclusion. Self-regulation development can lead to academic performance and increased self-control in the digital world. When examining the effects of distance learning and developing programs to enhance online learning, meaningful parameters for measuring adolescentsʼ social media integration into their everyday activities may be required.